Steric hindrance modulated efficient thermally activated delayed fluorescence with non-linear optical, ferroelectric and piezoelectric properties - Dutta, Madhusudan; Chatterjee, Abhijit; Deka, Nilotpal; Tanwar, Riteeka; Mishra, Vishnu; Saha, Arindam; Mandal, Pankaj; Boomishankar, Ramamoorthy; Hazra, Partha (Chemical Science, 2025)
Multi-carbazole-based benzonitrile systems are efficient thermally activated delayed fluorescence (TADF) materials for organic light-emitting diodes (OLEDs). However, they suffer from low PLQY due to the large dihedral angle arising from steric crowding. Addressing this challenge, we demonstrate a potent strategy to engineer steric crowding in this work. To achieve our goal, we have designed three luminogens, namely, CzPHCN, tCzPHCN and Cz2CzPHCN based on phenanthrene-9,10-dicarbonitrile (PHCN), as an acceptor core to minimize the steric hindrance between the donor groups. Among the three luminogens, tCzPHCN exhibits a maximum PLQY of 86% and the highest RISC rate of 3.5 x 105 s-1, the underlying cause being the least dihedral angle of 45.72 degrees and suppressed intermolecular interaction due to the presence of the bulky tert-butyl group. Interestingly, our QM/MM calculations and experimental evidence suggest that the RISC process of both CzPHCN and tCzPHCN takes place via a hot exciton channel. Unlocking a new realm of applications, the unique non-centrosymmetric space group (Cmc21) of CzPHCN offers excellent SHG with a chi(2) value of 0.21 pm V-1 at 1320 nm. In addition to this, the molecule depicts good ferroelectric (PS = 0.32 mu C cm-2), piezoelectric energy harvesting (VOC = 2.8 V) and two-photon absorption properties.